A Novel Color Image Encryption Scheme Using Rectangular Transform-Enhanced Chaotic Tent Maps - Xiaolin Wu (IEEE Access, 2017)
In recent years, the chaos-based cryptographic algorithms have attracted a lot of attention. Specially, chaotic tent map (CTM)-based schemes show some good performances in randomness properties and security level. However, several shortcomings still can be found from them. In this paper, based on the security analysis of the pure CTM-based scheme, we propose a novel image encryption algorithm by using the combination of the rectangular transform and the CTM principle. It encrypts the three channels of the plain image at the same time, and these channel encryptions associate with each other. In addition, by generating the key streams related to both the secret keys and the plain image, its key-sensitivity has been further improved. The security of the proposed scheme has been verified by security analysis and experimental evaluations, and our results show that many drawbacks of pure CTM-based schemes have been overcome.